STUDIES ON THE EFFECT OF SUPPLEMENTATION OF AREA SPECIFIC MINERAL MIXTURE ON MICRO MINERAL STATUS AND CYCLICITY IN POST-PARTUM ANESTROUS COWS - JANA, SONALI; VERMA, M S; WADHWA, D; SHARMA, K B; KUMAR, R (The Indian Journal of Animal Reproduction, 2023)
The present study was conducted to identify possible trace mineral deficiencies causing anestrus and prolonged post-partum anestrus and evaluate the effect of strategic supplementation of Area Specific Mineral Mixture (ASMM) in these cases. The animals selected for study were categorized under three groups Group I- Control animals (anestrous cows of 90 days and above), Group II- Anestrous animals (anestrous of 90 days and above) and Group Ill- Pleuriparous animals (8 to 9 months of gestation) from Livestock Farm of CSKHPKV, Palampur consisting of 10 animals in each group. Parallel study was also conducted on animals from nearby villages of Panchrukhi block of District Kangra in the state of Himachal Pradesh consisting of 4, 11 and 6 cows in Group I, II and Ill respectively. The animals of Group II and Group Ill were supplemented with specially formulated Area Specific Mineral Mixture @ 50 gm/animal/day until the animals attained estrus whereas animals of Group I were kept as control. Anestrous group of cows from field showed a significant (p<0.05) increase in average plasma iron concentration on day 90 (2.94 00.19 ppm) in comparison to control group (2.13 0 0.18 ppm). Significant (p<0.05) increase in average plasma copper concentration was observed in anestrous group of cows from day 30 (0.71 0 0.10 ppm) and day 60 (0.84 0 0.13 ppm) in comparison to control group on day 30 (0.25 0 0.04 ppm) and day 60 (0.29 0 0.11 ppm) respectively. An estrous group of cows from field also showed significant (p<0.05) increase in average plasma copper concentration on day 60 (0.94 0 0.11 ppm) in comparison to control group (0.28 0 0.06 ppm). Group II farm animals showed significant increase in average plasma zinc and cobalt concentration on day 30 and day 90 after strategic mineral mixture supplementation as compared to control group. In Group II farm animals, 7 out of 10 cows (70%) exhibited estrus and on an average animals came into heat after 35 days of mineral supplementation. In Group Ill of farm also 7 out of 10 cows (70%) came into heat and on an average animals came into heat 60 days of mineral supplementation. In Group II of field, 8 out of 11 cows (72.72%) came into heat,whereas in Group Ill of field only 2 out of 6 cows (33.33%) came into heat following strategic mineral supplementation. No animals from control group in farm as well as field came into heat during the period of study.